Evaluation of anode materials in sonoelectrochemistry processes: Kinetic, mechanism, and cost estimation. (November 2022) - Zhou, Yongyue; Cui, Mingcan; Ren, Yangmin; Lee, Yonghyeon; Ma, Junjun; Han, Zhengchang; Khim, Jeehyeong
Abstract: Eco-friendly pollutant treatment technology has a developing tendency in future. The combination of ultrasound (US) and electrochemical (EC) is a promising technology, because they are efficient, clean and environmentally friendly. In this study, the impacts of anode material have been investigated in US (300 kHz) and EC (10V) system. The results of all systems revealed that the kinetic constant decreased with increasing pH. The results are also shown that ΔG # > 0 and ΔH # > 0 during PCP degradation in EC or US-EC systems are non-spontaneous and endothermic reactions. Meanwhile, in the US-EC system, TiO2, Ti4 O7, PbO2, SnSb, RuIr, and BDD, except for TiO2, all the anode materials showed a synergistic index (SI) of 106–197%, and the activation energies were 19.32, 33.4, 33.74, 32.84, 10.41, 36.44 kJ mol −1, respectively. In EC and US-EC systems, PCP can be completely mineralized by BDD anode within 30 min. TBA scavenger experiments verified that hydroxyl radicals were the main oxidant in each system using BDD and PbO2 anode. As a result of estimating the cost according to the anode material when removing PCP using the EC or US-EC system, BDD was the smallest in the two systems, 1.58 and 1.12 $ m −3, respectively. Finally, this study may serve as a reference for implementation of US-EC system in wastewater treatment. Graphical abstract: Image 1 Highlights: Identification of reaction rate change through OEP analysis according to pH of anode material. Derivation of PCP decomposition activation energy and thermodynamic parameters. The mechanism that OH as a major oxidant in EC and US/EC system was confirmed. Determination of optimal combination of US and EC anode materials through economic analysis.